2020
DOI: 10.1186/s12871-020-01190-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the impact of propofol versus sevoflurane on early postoperative recovery in living donors after laparoscopic donor nephrectomy: a prospective randomized controlled study

Abstract: Background Enhancing postoperative recovery of the donor is important to encourage living kidney donation. We investigated the effects of anesthetic agents (intravenous [IV] propofol versus inhaled [IH] sevoflurane) on the quality of early recovery of healthy living kidney donors after hand-assisted laparoscopic nephrectomy (HALN) under analgesic intrathecal morphine injection. Methods This single-center, prospective randomized contr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…TIVA is particularly useful in some situations where inhalational anesthesia is contraindicated or may interfere with the operation. Several recent studies also showed that TIVA leads to better outcomes and even relieves postoperative pain compared with inhalant anesthesia [ 7 , 8 ]. Nevertheless, many anesthesiologists prefer volatile anesthesia (VA) because it is relatively easy to use, especially in short-duration surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…TIVA is particularly useful in some situations where inhalational anesthesia is contraindicated or may interfere with the operation. Several recent studies also showed that TIVA leads to better outcomes and even relieves postoperative pain compared with inhalant anesthesia [ 7 , 8 ]. Nevertheless, many anesthesiologists prefer volatile anesthesia (VA) because it is relatively easy to use, especially in short-duration surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Propofol produces less postoperative nausea and vomiting, a better sense of well-being, and a better quality of postoperative recovery. 26 - 28 According to the previous studies, the emotional state, which was evaluated using psychometric test, was significantly better after propofol-based anesthesia than sevoflurane-based anesthesia, 27 and the quality of recovery, including physical comfort, emotional state, physical independence, psychological support, and pain, was also significantly greater in the propofol group than in the sevoflurane group. 28 Second, although the pathophysiology and mechanism of POD have not yet been clearly determined, anti-inflammatory and anti-apoptotic properties of propofol may contribute to the lower incidence of POD compared with sevoflurane.…”
Section: Discussionmentioning
confidence: 93%
“…Another study showed that propofol reduces anxiety more than midazolam (25). This could be explained by a unique effect of propofol on the sense of well-being (27,28). The increase in dopamine levels in the nucleus accumbens is associated with the feeling of wellbeing in propofol patients (a phenomenon seen in drug abusers with pleasure-seeking behavior), (29).…”
Section: Discussionmentioning
confidence: 99%